Analisa Patah Housing Flywheel Mesin Diesel Dump Truck Berdasarkan Sifat Fisik dan Mekanik Material - Pramono, Yanuwar Ilpan; Krisnaputra, Radhian; Setyana, Lilik Dwi; Hendaryanto, I. Aris (Jurnal Teknologi dan Rekayasa Alat Berat, 2024)
This research aims to identify the causes of material failure in the flywheel housing of diesel engines used in dump trucks in corporate sectors such as mining, plantations and infrastructure in Indonesia. Through mechanical testing which includes visual observations, tensile, impact and hardness tests, as well as microstructural observations and chemical composition analysis, this research found that the flywheel housing material has brittle properties. The test results show the highest tensile strength of 23.021 MPa, the average impact value of 0.0417 J/mm2, and the average hardness value of 106.708 VHN. The microstructure of the flywheel housing material is dominated by the Al-Si alloy element, which makes the material tend to be brittle. Several factors that can cause cracks in the flywheel housing include the work environment, material properties, lack of maintenance, and operational errors.